Chronic Sleep Restriction in Developing Male Mice Results in Long Lasting Behavior Impairments - Saré, Rachel Michelle; Song, Alex; Levine, Merlin; Lemons, Abigail; Loutaev, Inna; Sheeler, Carrie; Hildreth, Christine; Mfon, Angel; Cooke, Spencer; Smith, Carolyn Beebe (Frontiers in Behavioral Neuroscience, 2019)
Sleep abnormalities are prevalent in autism spectrum disorders (ASD). Moreover, the severity of ASD symptoms are correlated with the degree of disturbed sleep. We asked if disturbed sleep during brain development itself could lead to ASD-like symptoms, particularly behavioral manifestations. We reasoned that sleep is known to be important for normal brain development and plasticity, so disrupted sleep during development might result in changes that contribute to behavioral impairments associated with ASD. We sleep-restricted C57BL/6J male mice (beginning at postnatal day 5 (P5) and continuing through P52) 3 hours per day by means of gentle handling and compared the data with a stress group (handled every 15 min during the 3-hour period) and a control group (no additional handling). From P42-P52, we assessed the behavioral effects of sleep-restriction in this pre-recovery phase. Then, we allowed the mice to recover for 4 weeks and tested behavior once again. Compared to the control group, we found that sleep restricted-mice had long-lasting hypoactivity, increased anxiety, and impaired social behavior; repetitive behavior was unaffected. These behavior changes were accompanied by an increase in the downstream signaling products of the mammalian target of rapamycin pathway. These data affirm the importance of undisturbed sleep during development and show that, at least in this model, sleep-restriction can play a causative role in the development of behavioral abnormalities. Assessing and treating sleep abnormalities in ASD may be important in alleviating some of the symptoms.